Research on preparing preservice teachers to work effectively with emergent bilinguals - Freeman, Yvonne S.; Freeman, David E. (Bingley, U.K. : Emerald, 2014)
Teacher educators need to be able to not only teach preservice teachers how to teach language arts, math, social studies, or science, but also to teach the language their students need to talk, read, and write about these subjects. Despite this need, there is a lack of research on how best to prepare preservice teachers to teach emergent bilinguals. In this book, teacher educators from institutions across the U.S. report their research with preservice teachers in large cities, suburban communities, and rural border areas. In each chapter, the authors explain what they have learned as they have conducted research on education for preservice teachers who will teach emergent bilinguals in mainstream, bilingual, and ESL.
Pedagogies of discomfort : shifting preservice teachers' deficit orientations toward language and literacy resources of emergent bilingual students / Suniti Sharma, Althier Lazar -- Developing deeper understandings of diversity : service learning and field experiences combine for generative learning of bilingual/ESL preservice teachers / Minda Morren López, Lori Czop Assaf -- "Porque sé los dos idiomas." Biliteracy beliefs and bilingual preservice teacher identity / Sandra I. Musanti -- Monolingual teacher candidates promoting translingualism : a self-study of teacher education practices project / David Schwarzer, Mary Fuchs -- Discovering best practices for bilingual teacher preparation : a pedagogy for the border / Alcione N. Ostorga, Peter Farruggio -- Modeling collaborative teaching in teacher education : preparing pre-service teachers to teach all students / Tatyana Kleyn, Jan Valle -- Preparation to practice : what matters in supporting linguistically responsive mainstream teachers / María Estela Brisk, Anne Homza, Janet Smith -- Preparing Latina/o bilingual teachers to teach content in Spanish to emergent bilingual students on the US-Mexico border / Alma D. Rodríguez, Sandra I. Musanti -- A self-study of teacher educator practice : strategies and activities to use with authentic texts / Mary Soto -- Annotated lesson plans : the impact on teacher candidate preparation for emergent bilingual students / Craig A. Hughes -- "Performing goofiness" in teacher education for emergent bilingual students / Mary Carol Combs.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Education -- Language Experience Approach; Education -- General; Teachers' classroom resources & material; Education; Teachers -- Training of -- United States; Education, Bilingual -- United States